2019
DOI: 10.3389/fphys.2019.00416
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Optical Diagnostics of the Microhaemodynamics in Upper and Lower Limbs

Abstract: The introduction of optical non-invasive diagnostic methods into clinical practice can substantially advance in the detection of early microcirculatory disorders in patients with different diseases. This paper is devoted to the development and application of the optical non-invasive diagnostic approach for the detection and evaluation of the severity of microcirculatory and metabolic disorders in rheumatic diseases and diabetes mellitus. The proposed methods include the joint use of laser Doppler flowmetry, ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…LDF is used for functional diagnostics of the blood microcirculation system, including diagnostics of socially significant diseases associated with the cardiovascular system. 11 In addition, this method allows one to evaluate oscillatory processes in the microcirculatory bed using data processing by the means of the Morlet wavelet. There are several frequency ranges that characterize the contribution of various factors to the LDF signal: endothelial (0.0095-0.021 Hz), neurogenic (0.021-0.052 Hz), myogenic (0.052-0.145 Hz), respiratory (0.145-0.6 Hz), and cardiac (0.6-2 Hz).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LDF is used for functional diagnostics of the blood microcirculation system, including diagnostics of socially significant diseases associated with the cardiovascular system. 11 In addition, this method allows one to evaluate oscillatory processes in the microcirculatory bed using data processing by the means of the Morlet wavelet. There are several frequency ranges that characterize the contribution of various factors to the LDF signal: endothelial (0.0095-0.021 Hz), neurogenic (0.021-0.052 Hz), myogenic (0.052-0.145 Hz), respiratory (0.145-0.6 Hz), and cardiac (0.6-2 Hz).…”
Section: Methodsmentioning
confidence: 99%
“…There are several frequency ranges that characterize the contribution of various factors to the LDF signal: endothelial (0.0095-0.021 Hz), neurogenic (0.021-0.052 Hz), myogenic (0.052-0.145 Hz), respiratory (0.145-0.6 Hz), and cardiac (0.6-2 Hz). 12 Analysis of skin blood flow fluctuations significantly aids understanding the physiological characteristics of the cardiovascular system, 13 and allows one to track pathological changes in various diseases, in particular in rheumatic diseases 11 and diabetes. 14,15 The research was carried out according to the following scheme shown in the figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The gradual decrease in the average lifetime parameters of the first and second decay components with the increase of the AGEs has been demonstrated by the incubation of the collagen gel and dentin in ribose [39]. Remarkably, no significant differences in lifetime parameters were found in measurements on skin of diabetic patients and healthy volunteers [153], whereas an increase in cutaneous fluorescence is indicative of the development of diabetic ulcers [108, 156].…”
Section: Optical Approaches In Diagnosticsmentioning
confidence: 99%
“…Optical spectroscopy has been thoroughly studied over the past years to characterize its diagnostic accuracy in diagnosing microcirculation disorders [19] or cancer on a wide variety of organs such as liver [20,21], breast [13], colon [9,22], skin [3,23,24], cervix [25,26], esophagus [27] or bronchi [28]. Those research teams decided either to use off-the shelf devices, or to develop their own devices.…”
Section: Introductionmentioning
confidence: 99%